The Concept of Qanaah as a Coping Strategy in Islamic Guidance and Counseling for Family Economic Stress - Muhammad Syaiful Muiz; Rada Walimatul Mabruroh; Hendrik Sulistiawati; Ribut Nila Indriani; Chandra Duwita Ela Pradana (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the concept of qana'ah as a coping strategy within Islamic guidance and counseling in addressing family financial stress. This research employs a qualitative descriptive approach utilizing a literature review method. The subjects of this study comprise scientific literature published between 2021 and 2026. Data collection techniques involve evaluating theories and research findings, alongside analyzing various publications relevant to the research problem. The findings indicate that qana'ah is classified as a form of emotion-focused coping that effectively supports individuals in managing emotional distress by fostering emotional stability, reinforcing the meaning of life, and enhancing gratitude. The integration of qana'ah values into the Islamic guidance and counseling process can be implemented through bibliotherapy and reframing techniques, which serve as a form of spiritual-based cognitive restructuring. The novelty of this study lies in the integration of qana'ah as a coping strategy to resolve family financial stress, an area that remains minimally explored in previous literature. Consequently, these implications suggest that Islamic guidance and counseling professionals can develop more holistic interventions by blending psychological approaches with spiritual values. This synthesis aims to enhance inner emotional strength and psychological well-being among families experiencing financial hardship.